Development and Test Analysis of the RV Reducer Comprehensive Performance Test Platform - Yi Qiu; Yijing Guo; Fengqiang Gao (Jixie chuandong)
The control accuracy of industrial robot depends on the comprehensive performance of RV reducer， which is the core component of industrial robot. At present， there is a lack of testing products for the performance of RV reducer in the market， the existing testing system has single function，which can't satisfy the requirements of industrial robot production and research. By analyzing the structure and working principle of RV reducer， the measurement method of performance parameters such as transmission error， transmission efficiency and torsional stiffness of RV reducer is intensively studied， an automatic measurement platform of RV reducer dynamic transmission performance is designed， it provides reference and basis for mechanical design and performance test of RV reducer.